The effect of EIB operations on private sector lending outside the European Union - Matteo Gatti; Denis Gorea; Andrea Presbitero (European Investment Bank (EIB), 2023)
Does an increase in lending by multinational development banks affect the private lending activity in developing countries? We show that this is indeed the case using data on loans and investments by the European Investment Bank (EIB) in combination with data on syndicated loans. We find that a pronounced increase in EIB operations is followed by a surge in the number and volumes of syndicate loans in countries outside the European Union. Our results suggest that multinational banks can incentivize private sector lending by playing an important role in signaling to private markets that borrowers in emerging and developing countries are safe.
Keywords: F21; F34; H81; 330; European Investment Bank; Financial assistance; Financial conditions; Public and private lending; Syndicated loans